Seleção e produção de ferros fundidos nodulares: solidificação, formação microestrutural e propriedades mecânicas - Silva, Marcos Vinicius de Souza da (Universidade Federal de São Carlos, 2025)
Ductile Cast Iron (DCI) features precipitation of graphite as nodules in a ferritic and/or pearlitic matrix as its main characteristic. During processing, the significance of overheating (OH) is related to the nucleation and growth, final microstructure, defect formation, and solidification time. A DCI containing 3.9%C, 2.9%Si, and 0.2%Mn has been selected for this study through TOPSIS analysis. After manufacturing DCI ingots obtained by varying 2 levels of OH (pouring temperatures of 1-1390°C and 2-1450°C), samples have been analyzed regarding their surface (S) and center (C). These samples have been characterized regarding graphite morphology by determining its fraction, average size, count, nodularity, and composition, the type of matrix formed through fractions of pearlite, ferrite, carbides, and mechanical properties. It was demonstrated that larger graphite nodules form at the center of the Fe-3.9C-2.9Si-0.2Mn alloy due to lower cooling rates and extended C diffusion, with overheating further enlarging nodules by lengthening the solidification times. Increase overheating has increased Fe migration to the graphite nodule surface during solidification and lowered the resulting graphite fraction. Higher nodularity improves ductility, with more spherical nodules in the OH-2 condition balancing higher pearlite fractions, resulting in similar ductility (26%) comparing samples at surface for both overheating levels.
Selection and production of ductile cast irons: solidification, microstructural formation, and mechanical properties
Keywords: Ferro fundido nodular; TOPSIS; Seleção de materiais; Superaquecimento; Taxa de resfriamento; Microestrutura; Solidificação; Ductile cast Iron; Materials design; Overheating; Microstructure; Cooling rate; Solidification; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO